Determine the Prevalence and Associated Risk Factors of Contrast Induced Nephropathy in Patients Undergoing Percutaneous Coronary Intervention (Medical Forum Monthly, 2020)
Objective: To examine the prevalence and associated risk factors of contrast induced nephropathy in patients undergoing multi-vessel percutaneous coronary intervention.Study Design: Prospective/ObservationalPlace and Duration of Study: This study was conducted at the Department of Cardiology, Bolan Medical Complex Hospital Quetta from July 2019 to December 2019.Materials and Methods: One hundred and fifty patients of both genders with ages 20 to 80 years undergoing percutaneous coronary intervention were enrolled in this study. Patient’s detailed demographics were recorded after written consent. Contrast induced nephropathy was defined as serum creatinine >0.5mg/dl from baseline value. Risk factors associated with contrast induced nephropathy were examined.Results: There were 105 (70%) males and 45 (30%) were females with mean age 57.64±7.28 years. Contrast induced nephropathy was found in 26 (17.33%) patients. Anemia, diabetes mellitus, hypertension, contrast volume >150ml, congestive heart failure and age >70 years were significantly associated risk factors of contrast induced nephropathy with p-value <0.05.Conclusion: The incidence of contrast induced nephropathy in patients undergoing percutaneous coronary intervention is high. Significant risk factors for contrast induced nephropathy were anemia, age >70 years, diabetes mellitus, contrast volume >150ml and heart failure.